MINIMARKETS EXISTENCE ON SALES TURNOVER OF THE TRADITIONAL SHOPS - Neni Murniati (TRIKONOMIKA, 2020)
This paper summarizes the results of a study that explains the impact of minimarkets existence on the sales turnover of traditional shops in Ciledug Subdistrict, Cirebon Regency in 2017, West Java, Indonesia. Through a statistical method - called the difference test - the existence of minimarkets in Ciledug Subdistrict has significantly reduced the sales turnover and reduced the number of buyers of the traditional shops, on the other hand the number of working hours of traditional shops has increased. This study also uses the regression model to explain the effect of the number of buyers, traditional shops’ working hours, and the distance between traditional shops to the nearest minimarkets on the sales turnover of traditional shops. This study shows that all independent variables simultaneously significant affected on the sales turnover of traditional shops. Partially, the number of buyers and the distances between traditional shops to the nearest minimarkets significantly influence the sales turnover of traditional shops, but the working hours of the traditional shops does not has a significant effect.